The influence of physical exercise on loneliness of college students: mediating and moderating roles - Yadong Liang; Lijun Wang; Xingbin Du (Frontiers in Psychology)
ObjectiveTo explore the relationship between physical exercise and loneliness of college students and its mechanism, and to analyze emotional self-efficacy as a mediating variable and psychological elasticity as a moderating variable.MethodsIn this study, the Physical Exercise Scale, the UCLA Loneliness Scale, the Emotion Regulation Self-Efficacy Scale (RES) and the psychological elasticity Scale were selected and used in a cross-sectional design to conduct a comprehensive survey of 850 college students from five different schools, for variables such as gender, grade, major, and place of origin. In the subsequent stage of data processing and analysis, SPSS 27.0 was used to descriptive statistics and correlation analysis to carry out a series of processing and analysis work on the collected relevant data. On this basis, in order to explore the mediating role of emotion self-efficacy in the relationship between physical exercise and loneliness more deeply, the researchers further constructed a structural equation model using AMOS28.0 software. The mediation effect ERSE and its 95% confidence interval (CI) were tested using the bootstrap sampling method (5,000 times), which is mainly used to detail the path between variables.ResultsThere was a significant correlation between physical exercise, loneliness, emotional regulation self-efficacy, and psychological elasticity. The results of the direct effect analysis showed the direct predictive effect of physical exercise on the loneliness of college students was significant (β = −0.600, p < 0.001). The of the mediation effect analysis showed that the standardized coefficient of the path “physical exercise → emotional regulation self-efficacy” was 0.580 (p < 0.001), and the standardized coefficient of the path “emotional regulation self-efficacy → loneliness” was −0.474 (p < 0.001); psychological elasticity played a partial mediating role between physical exercise and loneliness in college students (β = −0.156, p < 001).ConclusionPhysical exercise can not only positively affect loneliness of college students, but also mediate and regulate self-efficacy and mental resilience through emotional regulation, respectively.